The Influence of Geopolitical Risks on Bilateral Trade Flows - Männistö, Emil (My University, 2023)
This thesis examines the impact of geopolitical risks on international trade flows. In recent times, geopolitical risks have risen to the forefront, influenced by critical events like the Ukraine-Russia war. Such risks include uncertainties in geopolitics, economics, and policy, with profound implications on global dynamics. The study focuses on analysing these risks from an international trade perspective, a key component of the global economy that enables nations to leverage comparative advantages and foster economic growth. Prior foundational work by Gupta et al. (2019) utilised the geopolitical risk index from Caldara and Iacoviello (2022) to analyse the relationship between geopolitical uncertainties and trade dynamics. However, this thesis extends the literature by focusing on the diverse differences within the geopolitical risk index, specifically between geopolitical acts and threats, and their varied impacts on industry-specific trade flows. Employing a gravity model analysis across nine sectors, the thesis aims to illustrate how actual geopolitical acts and potential threats influence trade flows differently. This approach allows for a comprehensive exploration of how various industries respond to these risks, highlighting their sensitivities and resilience to geopolitical disruptions. Our results suggest that geopolitical risks are important to disaggregate to its subindexes, geopolitical threats and geopolitical acts, because of their opposing effects. Furthermore, industries like food, textiles, and vehicles could be more resistant to geopolitical risks. The findings of this research are set up to offer significant insights for businesses in the international market, aiding in the development of strategies to navigate a geopolitically volatile environment. Additionally, it contributes to the academic discourse by filling gaps in existing literature, particularly regarding the differential effects of geopolitical risks on international trade flows, and offers valuable perspectives for policymakers and scholars
Keywords: geopolitical risks, international trade, gravity model, bilateral trade, geopolitical threats, geopolitical acts